Implementation of Working Hours Regulation for Civil Servants During the Month of Ramadan at the Secretariat of the Regional House of Representatives of Banjar City - Adrian Ramadan; Jesita; Novia Ramadani Sugiarto; Yeisa Nur`arifah; Ii Sujai (Jurnal Dialektika: Jurnal Ilmu Sosial, 2025)
Adjustment of working hours during the month of Ramadan in the West Java Provincial Government, including Banjar City, is a form of adaptive policy to support ASN in carrying out worship while fulfilling official duties. This policy is based on Circular Letter of the Governor of West Java Number 061.2/PK.01/BKD concerning Determination of Working Hours During the Month of Ramadan and followed up by the Banjar City Government through Circular Letter of the Mayor of Banjar City Number 800/116/BKPSDM/2023. This study aims to analyze the impact of the implementation of working hour adjustments on ASN discipline and performance at the Banjar City DPRD Secretariat. The method used is descriptive qualitative with data collection techniques through observation, interviews, and documentation. The results showed that this policy has a positive impact on ASN discipline, especially in the aspects of attendance and compliance with working time. However, the reduction in working hours raises challenges in maintaining productivity. ASN is required to adjust its work rhythm and time management so that output remains optimal. This Matter makes a new contribution to the study of ASN management because it highlights performance in the context of temporary and religious working time. This research is the basis for formulating contextual and responsive personnel policies.